Factors that interfere with users’ adherence to pap smear within the PHC (Research, Society and Development, 2022)
Objective: to identify factors that interfere with users' adherence to Pap smear within the PHC. Methodology: This is a research with a qualitative approach, of the descriptive type, along the lines of an integrative literature review. In the result of crossing the descriptors in Health Sciences (DeCS) and searching the main databases BDENF, LILACS, MEDLINE and PUBMED, a total of 18 selected articles was obtained through a detailed and exhaustive reading. Results: In the synthesis, three themes emerged: knowledge and practice about Pap smear, barriers to accessing Pap smear, beliefs and feelings regarding Pap smear, followed by an integrated discussion on the implications of these topics. Conclusion: It was concluded that differentiated actions by nurses are essential, including the adequacy or implementation of educational and participatory activities, the clarification of women about the Pap smear along with plans to overcome obstacles to access and the problematization of feelings and beliefs that envelop them; These factors can result in setbacks for the prevention of cervical cancer.